2012
DOI: 10.1080/0309877x.2011.606898
|View full text |Cite
|
Sign up to set email alerts
|

The emotional impact of being recently diagnosed with dyslexia from the perspective of chiropractic students

Abstract: Increased awareness and improved tests have contributed to the identification of rising numbers of dyslexic students entering higher education in the United Kingdom. Nearly half of these students are not diagnosed until they start their HE courses. Studies of experiences of dyslexic students diagnosed as children exist; however, there is little comparable information on dyslexic students diagnosed as adults.This qualitative study explores the experiences of six students diagnosed with dyslexia after starting t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…These are in accordance with other researchers' fi ndings (Goodwin & Thomson, 2004;Peer, 2006;Thomson & Chinn, 2001;Young Kong, 2012). One of the participants said:…”
Section: Personal Assetssupporting
confidence: 92%
See 1 more Smart Citation
“…These are in accordance with other researchers' fi ndings (Goodwin & Thomson, 2004;Peer, 2006;Thomson & Chinn, 2001;Young Kong, 2012). One of the participants said:…”
Section: Personal Assetssupporting
confidence: 92%
“…Like typically developing others, they also long to receive recognition and approval from their peers and signifi cant others (Hales, 2001;Jordan, 2002;Reid, 2004). Disability related name calling hurts them (Nalavany et al, 2011;Reid, 2004;Young Kong, 2012) and social supports could enhance their overall coping (Galloway, 2006). Being able to do something which is within their abilities or strengths and that they are passionate about, results in positive self-perceptions (Burden, 2004;Goodwin & Thomson, 2004).…”
Section: Personal Assetsmentioning
confidence: 99%
“…The two themes would appear to be linked, as participants described relief at finding an alternative explanation for why life in the social and emotional worlds has been such a struggle, reallocating blame from self to the condition of AS and creating a less problem-saturated narrative. This reaction resembles the “not guilty verdict” in Punshon et al (2009) and the “liberating revelation” that can result from a diagnosis of dyslexia, where there is a shift in thinking away from self-blame (Kong, 2012). For some participants, emotional reactions were complex, often combining positive and negative feelings, as illustrated by one participant, who reported, “I cried like a baby and felt like dancing with joy at the same time.…”
Section: Discussionmentioning
confidence: 69%
“…This research does not monitor the long-term effects of the identification of dyslexia. It is interesting to note that Ingesson (2007) and Young Kong (2012) found that, with time, the self-esteem of individuals with dyslexia grew and their difficulties became less of an issue. In the current study, the parents were interviewed shortly after diagnosis and their feelings and reactions were therefore raw.…”
Section: Discussionmentioning
confidence: 99%